Hubungan antara Self Efficacy dan Kreativitas dengan Minat Berwirausaha - Hapsah, Rifqi; Savira, Siti Ina (Universitas Negeri Surabaya, 2015)
The purpose of this research is to examine the correlation between self efficacy and interest in entrepreneurship, the correlation between creativity and interest in entrepreneurship and, the correleation between self efficacy and creativity with interest in entrepreneurship. This research used quantitative approach with correlation method. Scales of self efficacy, creativity and entrepreneurship were given to 82 college students of School of Psychology from four different years who were selected using random technique sampling. This research applies 5% significant level. The data were analyzed using product moment, and multiple-correlation test. The significant value from correlation between self-efficacy and interest in entrepreneurship is 0,000, with correlation index of 0.703, which means that there is a significant relationship between self-efficacy and interest in entrepreneurship. The significant value from correlation between creativity and interest in entrepreneurship is 0,008, with correlation index of 0.292. It can be concluded that there is a significant relationship between creativity and interest in entrepreneurship. The result of multiple-correlation test shows correlation coefficient between self efficacy and creativity with entrepreneurship as much as 0,757 and Fh (57,2) > Ftabel (3,112). Therefore, it can be concluded that there is a significant correlation between self efficacy and creativity with interest in entrepreneurship.Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan self efficaccy dengan minat berwirausaha, hubungan kreativitas dengan minat berwirausaha, dan hubungan self efficaccy dan kreativitas dengan minat berwirausaha. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Skala self efficacy,Â skala kreativitas, dan skala minat berwirausaha diberikan kepada 82 subjek penelitian, yaitu mahasiswa Psikologi dari 4 angkatan yang dipilih dengan teknik random sampling. Peneliti menggunakan taraf kesalahan 5% dan metode analisis data korelasi product moment dan uji korelasi ganda. Analisis data menunjukkan terdapat hubungan signifikan antara self efficacy dengan minat berwirausaha sebesar 0,000, dengan indeks korelasi sebesar 0,703. Terdapat hubungan yang signifikan pula antara kreativitas dengan minat berwirausaha sebesar 0,008, dengan indeks korelasi sebesar 0,292. Hasil uji korelasi ganda menunjukkan koefisien korelasi antara self efficacy dan kreativitas dengan minat berwirausaha sebesar 0,757, dan Fh (57,2) > Ftabel (3,112), sehingga dapat disimpulkan bahwa ada hubungan yang signifikan antara self efficacy dan kreativitas dengan minat berwirausaha.